Discourse Structure and Linguistic Features of Academic Textbooks: A Qualitative Analysis - Dwi Gea; Juni Bate’e; Epifania Harita; Afore Harefa (Indonesian Journal Publisher, 2026)
This study examines the discourse structure and linguistic features of selected chapters in Psycholinguistics: Introduction and Applications (second edition) by Menn and Dronkers. Academic textbooks play a central role in shaping how disciplinary knowledge is organized and understood, yet relatively little attention has been paid to how psycholinguistics textbooks manage structure and language complexity for learners. The objective of this study is to identify organizational patterns, cohesion and coherence strategies, and indicators of linguistic complexity in the textbook. Using a qualitative discourse-analytic approach, purposively selected introductory and methods chapters were analyzed. Units of analysis included discourse moves, paragraphs, and sentences. The study combined close reading with analytical categories drawn from register and genre studies, focusing on rhetorical organization, cohesive devices, and syntactic and lexical features. The findings reveal a clear chapter-level structure resembling the Introduction–Method–Results–Discussion pattern, adapted for instructional purposes. The text makes frequent use of cohesive ties such as reference, conjunction, and lexical repetition to guide explanation. It also demonstrates dense noun phrases, nominalization, and specialized terminology that compress information while maintaining pedagogical clarity. The study concludes that psycholinguistics textbooks balance informational density with instructional accessibility, offering implications for textbook development and academic reading instruction.